Influential Article Review- The Implications of Authoritative Leadership and Mission Outcomes - Johnston, Ed; Kelly, Nina; Oliver, Fernando (Journal of Leadership, Accountability and Ethics, 2019)
This paper examines leadership. We present insights from a highly influential paper. Here are the highlights from this paper: This study examines how and when authoritarian leadership affects subordinates’ task performance. Using social exchange theory and power dependence theory, this study proposes that authoritarian leadership negatively influences task performance through leader-member exchange (LMX). This study further proposes that the effect of authoritarian leadership on LMX is stronger when a subordinate has less dependence on a leader. A two-wave survey was conducted in a large electronics and information enterprise group in China. These hypotheses are supported by results based on 219 supervisor-subordinate dyads. The results reveal that authoritarian leadership negatively affects subordinates’ task performance via LMX. Dependence on leaders buffers the negative effect of authoritarian leadership on LMX and mitigates the indirect effect of authoritarian leadership on employee task performance through LMX. Theoretical contributions and practical implications are discussed. For our overseas readers, we then present the insights from this paper in Spanish, French, Portuguese, and German.